Unmet Health Needs – Selected Administrative Law Aspects - Mełgieś, Katarzyna; Miaskowska-Daszkiewicz, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
This paper discusses the concept of unmet health needs in the perspective of the tasks of public authorities creating the health care system. Starting from the concept of human health needs and their implementation within the health care system, the areas that have been normatively developed by the legislator in relation to the legal approach to the concept of unmet health needs have been indicated. In the part devoted to meeting unmet health needs, an exemplary review of instruments available to public authorities in this regard was made. The final conclusions indicate the usefulness of identifying health needs as unmet due to the lack of an available therapeutic method in the health care system, primarily in the light of the need to develop an effective system response to them.